Intramuscular immunization with a vesicular stomatitis virus recombinant expressing the influenza hemagglutinin provides post-exposure protection against lethal influenza challenge - Barefoot, Brice E. (2009)
Vaccines currently licensed for the prevention of seasonal influenza induce antibodies against the influenza hemagglutinin (HA) and neuraminidase (NA) contained in the vaccine preparation but require at least two weeks after immunization for the development of protective immunity. These vaccines do not induce protective responses quickly enough to blunt the effects of infection when administered after exposure. We have developed a novel vaccine based on recombinant vesicular stomatitis virus which expresses the influenza hemagglutinin (rVSV HA) and protects mice from lethal influenza challenge when the vaccine is administered intramuscularly at least 24 hours after delivery of the influenza challenge virus. To our knowledge this is the first vaccine that effectively protects animals from lethal influenza challenge when delivered by a systemic route after influenza exposure has occurred. The induction of HA-specific immune responses by the vaccine is necessary for full protection from challenge, because animals immunized with an empty rVSV vector were not protected equally. Our results are consistent with a model in which vaccination induces an immediate antiviral cytokine response, followed by development of humoral and cellular immune responses which act to reduce pulmonary viral loads and accelerate recovery. Consistent with this model, mice vaccinated with the specific vaccine rVSV HA had high levels of IFN-α in the serum by 24 hours after challenge/vaccination, developed serum neutralizing Ab to influenza two days prior to control animals, and had detectable anti-HA CD8 T cells present in the peripheral blood three days prior to control mice.